Studi tentang Nilai Pendidikan Karakter dalam QS. al-Ṣāffāt/37: 102-103 - Usman, Usman (JURNAL AL-QAYYIMAH, 2020)
This paper discusses the Value of Character Education in QS. al-Ṣāffāt / 37: 102-103. To obtain data, the researchers traced data through the library (library research) through searching books and research results related to the problem under study. The approach used in this research is the normative theological approach, psychological approach, and historical approach. The data analysis technique used is deductive namely data processing techniques by analyzing the data and information that have been obtained, but still scattered and then collected and analyzed so that the data and information are intact and can provide a true picture of the object under study. This data analysis technique is done by departing from general data and then drawing conclusions that are specific.The results found that QS. al-Ṣāffāt / 37: 102-103 commentators explain the story of the Prophet Abraham who was willing to slaughter his son named Ishmael for obedience and patience to obey God's commands through his dreams supported by obedience of the child to the commands of his parents. Character education in the verse is divided into three main points, namely: First. The method, the method used is the method of command, dialogue, and example. Second. The principle, the principle used is the principle of integration, balance, rububiyah, and open. Third. Material, material taught is patience, obedience, politeness, and sincerity. With the wisdom contained in this verse, educators, especially parents can educate their children using the methods and methods of the prophets as exemplified by the prophet Ibrahim in educating their children to be children of character.